Making spatial-temporal marine ecosystem modelling better – A perspective. (November 2021) - Steenbeek, Jeroen; Buszowski, Joe; Chagaris, David; Christensen, Villy; Coll, Marta; Fulton, Elizabeth A.; Katsanevakis, Stelios; Lewis, Kristy A.; Mazaris, Antonios D.; Macias, Diego; de Mutsert, Kim; Oldford, Greig; et al.
Abstract: Marine Ecosystem Models (MEMs) provide a deeper understanding of marine ecosystem dynamics. The United Nations Decade of Ocean Science for Sustainable Development has highlighted the need to deploy these complex mechanistic spatial-temporal models to engage policy makers and society into dialogues towards sustainably managed oceans. From our shared perspective, MEMs remain underutilized because they still lack formal validation, calibration, and uncertainty quantifications that undermines their credibility and uptake in policy arenas. We explore why these shortcomings exist and how to enable the global modelling community to increase MEMs' usefulness. We identify a clear gap between proposed solutions to assess model skills, uncertainty, and confidence and their actual systematic deployment. We attribute this gap to an underlying factor that the ecosystem modelling literature largely ignores: technical issues. We conclude by proposing a conceptual solution that is cost-effective, scalable and simple, because complex spatial-temporal marine ecosystem modelling is already complicated enough. Highlights: Marine Ecosystem Models (MEMs) are rarely systematically validated and calibrated. This can potentially undermine the credibility and uptake of model output in the policy arenas where it is so direly needed. Suggestions to assess model skill, uncertainty, and confidence abound in the literature, but applications are mostly lacking. We identify the main technical hurdles that prevent the MEM community from moving forward, and specify a resolving framework. We call on the MEM community to create collaboratively such a framework to produce model results with more confidence.